Voluntary Donations and Public Expenditures in a Federalist System - Steinberg, Richard (American Economic Review, 1987)
[Proponents of the new federalism argue that nonprofit organizations and local governments will fully offset federal social service expenditure cutbacks. I analyze this proposition as a competitive game in which donations are motivated by private and public good considerations. I characterize the response of political-economic equilibrium to exogenous changes in federal expenditures when local voters are cognizant of donor reactions. Partial replacement is the most likely outcome, though others are possible.]